Uncertainty in Kinetic Energy Models for Rainfall Erosivity Estimation in Semi-Arid Regions - José Bandeira Brasil; Ana Célia Maia Meireles; Carlos Wagner Oliveira; Sirleide Maria de Menezes; Francisco Dirceu Duarte Arraes; Maria Simas Guerreiro (Hydrology, 2025)
The Brazilian semi-arid Northeast plays a critical role in regional hydrology, where rainfall is marked by pronounced temporal variability and short duration, presenting significant challenges for understanding and managing hydrological and erosive processes. This study aims to evaluate the performance of empirical models for estimating rainfall kinetic energy (KE) and erosivity index (EI30) in this region, for all events and erosive events, using high-resolution rainfall data collected at the Federal University of Cariri (UFCA), Ceará. A total of 283 natural rainfall events were analyzed, with KE and EI30 values calculated using multiple models: Wischmeier and Smith, USDA, Van Dijk, a temporal variation-based model (KE_VT), and a regional model developed for Brazil’s semi-arid zone, which served as the reference. The results show a predominance of small rainfall events (<5.2 mm), though maximum EI30 values exceeded 1300 MJ ha−1 mm h−1, highlighting the potential for extreme erosive events. Comparative analysis revealed that all international models significantly underestimated KE and EI30 values compared to the regional reference, with the KE_VT model showing the closest approximation (13% underestimation), for all events and erosive events. Statistical assessments using the Wilcoxon test, Nash–Sutcliffe efficiency, and Willmott concordance index confirmed the superior performance of the KE_VT, for all events and erosive events. These findings underscore the importance of considering intra-event rainfall variability and regional calibration when modeling erosivity in semi-arid climates, contributing to more effective soil conservation and hydrological planning.